PEMBARUAN ISLAM BIDANG HUKUM KELUARGA DAN RELEVANSINYA DENGAN TUNTUTAN EGALITER PRIA DAN WANITA - Hulaimi Azhari (IAIN Purwokerto, 2020)
In this paper explained the mechanism of renewal of Islam in the field of family law and its relevance to the egalitarian demands of men and women. This discussion is known that there is a difference between the Islamic period and the pre-Islamic period that has implications with the rule of law applied. The evils and misdeeds of the Arab jahiliah against women are the things that apply to the renewal of the law in the field of family law, such as marriage, polygamy, dowry, or inherition. The practice of marriage, which was performed in pre-Islamic times, has done a lot of harm to women. In those days, women were only considered a product or commodity that served to be traded. For example, the birth of a baby girl is a disgrace that is so shameful that it is considered to smear the face of the family. So sadistic, the newborn baby girl must be buried alive. In addition to the issue of inherited law, at that time the woman's right was exercised her right to obtain the inheritance left by her family. The conception of Islamic renewal in the field of family law in this study uses two approach methods, namely conventional methods, and contemporary methods. In the system of reform of the law of equality men and women can contain several things: equality of function and role, equality in enjoying sexual intercourse, equality in childcare, and the right to determine genetic engineering.